CELT - Corpus of Electronic texts - Turlough O'Riordan (RIDE, 2017)
This review addresses the ‘CELT - Corpus of Electronic texts’ archive, developed and housed at University College Cork, Ireland. CELT is a digital humanities archive – and arguably a scholarly platform – comprising 1600 documents. An account of its piecemeal historical evolution, spanning the emergence of the Digital Humanities in Ireland, is given in this review. This review contextualises the range of content (documents, editions, works), for the most part digital representations based on TEI, pertaining to the study of the Irish language and Celtic civilisation and culture, collected together in CELT – as it stood in April 2017.